UJI AKTIVITAS ANTIOKSIDAN EKSTRAK METANOL KULIT BUAH PISANG AMBON (Musa paradisiaca var. sapientum (L.) Kunt.) DENGAN METODE DPPH - Tullah, Mirna Hidaya; Marliana, Eva; Erwin, Erwin (JURNAL ATOMIK, 2023)
Test of antioxidant activity of ambon banana peel (Musa paradisiaca var. sapientum (L.) Kunt.) methanol extract has been done. Test were carried out using a UV-Vis spectrophotometer based on the DPPH radical scavenging method with positive control of vitamin C. Antioxidant activity was obtained based on the IC50 value of 104,31 mg/L. IC50 value indicates that the peel of Ambon banana (Musa paradisiaca var. sapientum (L.) Kunt.) has antioxidant activity which is included in the moderate category.